The application of theory of reasoned action in cyberbullying prevention program - Chin, Pau Yee; Wong, Gina Sie Suen; Lim, Jie Wei; Shea, Kher Yan; Tey, Chin Fui (2018)
Cyberbullying has been identified as an important and serious problem amongst adolescents in the Malaysia. However, there are only few cyberbullying prevention programs exist in Malaysia to curb with the issue of cyberbullying. Therefore, the present study developed a cyberbullying prevention program built on Theory of Reasoned Action (TRA) to examine whether video-based cyberbullying prevention program can significantly change adolescents’ behavior toward cyberbullying. In a paired sample t-test design where 384 secondary students with an age group of 15-17 years were randomly allocated to control group and experimental group. The result revealed that the present study had significantly increase adolescents’ knowledge and level of empathy toward cyberbullying after the intervention program. Even though the result showed no significant decrease in subjective norm between pre-test and post-test at experimental group, but respondents’ level of behavior intention and positive attitude toward cyberbullying had significantly decrease among pre-test and post-test for the experimental group. In conclusion, video-based cyberbullying prevention program is significant in changing adolescents’ behavior toward cyberbullying. This research is crucial to serve as an existing material for educators and researchers alike in applying the Theory of Reasoned Action in cyberbullying and to improve ways of curbing the cyberbullying issue.